Three Public Health Interventions Could Save 94 Million Lives in 25 Years: Global Impact Assessment Analysis. Issue 9 (27th August 2019) - Kontis, Vasilis; Cobb, Laura K.; Mathers, Colin D.; Frieden, Thomas R.; Ezzati, Majid; Danaei, Goodarz
Abstract : Background: Preventable noncommunicable diseases, mostly cardiovascular diseases, are responsible for 38 million deaths annually. A few well-documented interventions have the potential to prevent many of these deaths, but a large proportion of the population in need does not have access to these interventions. We quantified the global mortality impact of 3 high-impact and feasible interventions: scaling up treatment of high blood pressure to 70%, reducing sodium intake by 30%, and eliminating the intake of artificial trans fatty acids. Methods: We used global data on mean blood pressure levels and sodium and trans fat intake by country, age, and sex from a pooled analysis of population health surveys, and regional estimates of current coverage of antihypertensive medications, and cause-specific mortality rates in each country, as well, with projections from 2015 to 2040. We used the most recent meta-analyses of epidemiological studies to derive relative risk reductions for each intervention. We estimated the proportional effect of each intervention on reducing mortality from related causes by using a generalized version of the population-attributable fraction. The effect of antihypertensive medications and lowering sodium intake were modeled through their impact on blood pressure and as immediate increase/reduction to the proposed targets. Results: The combined effect of the 3 interventions delayed 94.3 million (95% uncertainty interval, 85.7–102.7) deaths during 25 years. Increasing coverage of antihypertensive medications to 70% alone would delay 39.4 million deaths (35.9–43.0), whereas reducing sodium intake by 30% would delay another 40.0 million deaths (35.1–44.6) and eliminating trans fat would delay an additional 14.8 million (14.7–15.0). The estimated impact of trans fat elimination was largest in South Asia. Sub-Saharan Africa had the largest proportion of premature delayed deaths out of all delayed deaths. Conclusions: Three effective interventions can save almost 100 million lives globally within 25 years. National and international efforts to scale up these interventions should be a focus of cardiovascular disease prevention programs. Abstract : Supplemental Digital Content is available in the text.